2009
DOI: 10.1016/j.bpj.2008.12.3900
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Shear Induces Conformation Change in Human Blood Protein von Willebrand Factor in Solution

Abstract: Many of the physiological functions of von Willebrand Factor (VWF), including its binding interaction with blood platelets, are regulated by the magnitude of applied fluid/hydrodynamic stress. We applied two complementary strategies to study the effect of fluid forces on the solution structure of VWF. First, small-angle neutron scattering was used to measure protein conformation changes in response to laminar shear rates (G) up to 3000/s. Here, purified VWF was sheared in a quartz Couette cell and protein conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
83
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(95 citation statements)
references
References 33 publications
9
83
0
3
Order By: Relevance
“…Furthermore, threefold prolonged measurement times were needed to achieve a reliable signal-to-noise ratio. The urea-containing buffer could only partly unfold the A2 domains and not all of them, thereby not all the cleavage sites may have been fully exposed (37). FCS measurements of the diffusion coefficients of rVWF-wt dimer and rVWF-G1629E dimer in nondenaturing and denaturing buffer confirmed the observation of partial unfolding (Fig.…”
Section: Effect Of the G1629e Mutation On The Cleavage Kineticssupporting
confidence: 54%
“…Furthermore, threefold prolonged measurement times were needed to achieve a reliable signal-to-noise ratio. The urea-containing buffer could only partly unfold the A2 domains and not all of them, thereby not all the cleavage sites may have been fully exposed (37). FCS measurements of the diffusion coefficients of rVWF-wt dimer and rVWF-G1629E dimer in nondenaturing and denaturing buffer confirmed the observation of partial unfolding (Fig.…”
Section: Effect Of the G1629e Mutation On The Cleavage Kineticssupporting
confidence: 54%
“…Furthermore, real-time measurements of the conformational dynamics of vWF in response to laminar shear flow in a Couette flow-cell, using a combination of small angle neutron scattering (SANS) spectroscopy and quantitative modeling, showed an irreversible conformational change in vWF, under hydrodynamic shear stress, at shear rates 3000 s 21 . 27 The observed conformational change was found to involve the exposure of hydrophobic domains at shear rates [2300 s 21 , as indicated by an increase in the binding affinity of the hydrophobic dye 1,10-bis(anilino)-4-,40-bis(naphtalene)-8,80-disulfonate (bis-ANS). 27 The shear-effect was more pronounced with increasing shear rate.…”
Section: Effects Of Shear Flow On Protein Structure and Functionmentioning
confidence: 99%
“…27 The observed conformational change was found to involve the exposure of hydrophobic domains at shear rates [2300 s 21 , as indicated by an increase in the binding affinity of the hydrophobic dye 1,10-bis(anilino)-4-,40-bis(naphtalene)-8,80-disulfonate (bis-ANS). 27 The shear-effect was more pronounced with increasing shear rate.…”
Section: Effects Of Shear Flow On Protein Structure and Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…VWF multimers can then mediate the adhesion of platelets. It has been shown that VWF multimers change from a globular to an elongated conformation under shear stress [10][11][12] and remain * chkiang@rice.edu in their activated, more adhesive state for hours [13]. Prolonged activation may coincide with the lateral association of VWF multimers into a fibrillar form of VWF [3,8,14].…”
mentioning
confidence: 99%